Analysis of the application of different plasmapheresis modes in immune diseases and acute rejection of kidney transplantation - ZHAO Yan; LEI Jie; LI Su-tong; DAI Wei (Linchuang shenzangbing zazhi)
Objective To investigate the application of selective single and double filtration plasmapheresis in immune diseases and acute rejection of renal transplantation, and to provide theoretical basis for clinical practice. Methods A total of 100 patients with immune diseases and acute rejection of renal transplantation, treated in Xi’an Central Hospital from April 2016 to March 2018, were enrolled in this study and divided into control group(n=50) and study group(n=50) The control group was given single-filtration plasmapheresis, and the study group was given double filtration plasmapheresis. The biochemical indexes, treatment, adverse reactions and prognosis of the two groups were compared. Results The plasma IgG and anti-glomerular basement membrane(GBM) antibody levels in the study group were lower than those in the control group after treatment, with statistically significant difference(P<0.05). The incidence of adverse reactions in the study group was significantly lower than that in the control group, with statistically significant difference(P<0.05). The hospitalization time and treatment cost of the patients in the study group had advantage over the control group, with statistically significant difference(P<0.05). The effective rate of renal function recovery in the study group was significantly higher than that in the control group, with statistically significant difference(P<0.05). Conclusions Selective double filtration plasmapheresis is performed in patients with immune diseases and acute rejection of renal transplantation, which can effectively improve the level of immunoglobulin IgG and anti-GBM antibody, shorten the treatment time, improve the effective rate of treatment and reduce the adverse reactions. The therapeutic effect is remarkable.